Three-Dimensional Transesophageal Echocardiography to Facilitate Transseptal Puncture and Left Atrial Appendage Occlusion via Upper Extremity Venous Access. (August 2015) - Aizer, Anthony; Young, Wilson; Saric, Muhamed; Holmes, Douglas; Fowler, Steven; Chinitz, Larry
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.